Prevalensi Stunting Anak Bawah lima Tahun di Puskesmas Al-Rajaiya, Distrik Ash-Shamayatayn - Taiz, Yaman: Prevalensi Stunting Anak Bawah lima Tahun di Puskesmas Al-Rajaiya, Distrik Ash-Shamayatayn - Taiz, Yaman - Mohammed, Haitham Taleb Salem; Nadhiroh, Siti Rahayu; Ali, Lamia A.S.; Moqbel, Hebah Hamood; Alarabi, Abdulhakeem Ali; Al-Maamari, Shakib Abdulbasit; Sari, Nur Mufida Wulan (Universitas Airlangga, 2023)
Background: Yemen is one of the low-income countries, with 80% of the population living below the poverty line and almost half the population lacks adequate access to nutritious food. The low-birth-weight rate is 24.6%, and the overall infant mortality rate is 47 per 1,000 births. The risk of death of newborns varies depending on social, demographic, and economic factors. Objectives: This study aims to evaluate the effect of the ongoing war on stunting prevalence among children under five years in Al-Rajaiya Health Center, Ash-Shamayatayn District - Taiz, Yemen. Methods: This study is an observational analytic with a cross-sectional design. It was conducted from January to June 2022, following purposive sampling gathered 254 participants. Results: The data revealed that the prevalence of severe stunting in 6- to 23-month-old children was higher in urban areas than in rural areas (45% vs. 43.7%); it was also higher in girls than in boys (58.4% vs. 30.3%). Furthermore, in 24- to 59-month-old children, it was higher in urban areas than in rural areas (50% vs. 12.5%) and higher in girls than in boys (42.9% vs. 19.6%) with p-value (0.040, 0.018, 0.001 and >.001) respectively. Conclusions: Findings demonstrated that the ongoing war has a significant effect on the stunting prevalence among children under five years. Early childhood undernutrition is linked to several adverse outcomes in adulthood, and it is plausible that undernutrition in early childhood may be a significant factor in explaining the health disparities faced by Yemeni children under five.